Household decision-making in rural Nepal : a study of the effects of gender roles and ethnicity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Rural Development at Massey University - Devkota, Durga (Massey University, 1999)
Gender disparity in household decision-making is common in developing countries. Ethnicity, culture and geographical location also influence decision-making processes in rural communities. Household decision-making processes in central rural Nepal were examined with a primary focus on gender roles and involvement in the context of three distinct ethnic communities--Brahmin/Chhetri, Gurung and Tharu. Three Village Development Committees (VDCs) of the Chitwan district of Nepal were purposively selected for the study. A combination of participatory rural appraisal (n=6), gender analysis (n=6), key informant interviews (n=14) and household socio-economic surveys (n=123) was used to gather information and data for the study. At the household level, men and women were interviewed separately. The results indicated that both men and women consistently carried out certain crop production activities. Other activities were either male or female dominated, but some activities were insensitive to gender and ethnicity. Ethnic variation impacted on gender roles and involvement of household members. For example, both males and females from the Brahmin/Chhetri and Gurung, and all family members from the Tharu, were involved in manure application to farmland. Fertiliser application was carried out by Brahmin/Chhetri and Tharu men. but jointly by the Gurungs. Crop harvesting was mostly completed by all household members, but with a low level of participation by men, and a high level of participation by women for all ethnic groups. Males dominated crop marketing in the Brahmin/Chhetri and Gurung communities, but this was jointly shared by the Tharus. Livestock-related work was primarily within the domain of women, but variation existed in gender roles across the ethnic groups. For example, Brahmin/Chhetri and Gurung men were less involved in grazing and fodder collection, but all members of Tharu households were jointly involved. Women were more involved than men in household management in all three ethnic groups, with the highest level of participation amongst the Tharu women. Decisions were reached by household members through general discussion. In some cases, however, such as in the marketing of large ruminants, the decision was made solely by the men. Household decision-making also depended on the level and source of income. Within the higher income Brahmin/Chhetri households decisions were largely made independently by males; for the lower income Gurung and the Tharu households joint decision-making was more common. Thus, the underlying male dominance in these communities tended to be related to income level. In relatively affluent households, women were largely restricted to household chores and were less involved in decision-making processes. With respect to crop income. the Gurung women exercised control, whereas the Brahmin/Chhetri males, and both men and women for the Tharus, had a dominant influence over such income. For all ethnic groups, men overwhelmingly dominated the access to agricultural and veterinary services, community activities, and off-farm employment opportunities. Rural and agricultural development activities in Nepal were shown not to be gender or ethnically neutral. However, the extent of this varies by activity. Thus, differences in gender and ethnic roles need to be specifically accounted for in rural policy formulation and planning. A pre-project analysis of gender and ethnicity involvement is recommended to provide better local knowledge of these factors before designing and implementing any project or developmental work. Keywords. Household decision-making. gender roles, ethnicity, gender analysis, participatory rural appraisal, Nepal, rural development
Keywords: Nepal; Home economics; Farm management; Decision making; Agriculture -- Social aspects; Sex role; Ethnicity; Rural women